Evaluation of Long‐Term Temperature Trend and Variability in CMIP6 Multimodel Ensemble. Issue 10 (20th May 2021) - Duan, Yanan; Kumar, Sanjiv; Kinter, James L.
Abstract: This study conducts a robust assessment of the Coupled Model Intercomparison Project Phase 6 to capture the observed temperature trends and variability at global and regional scales. The warming rate in the second half of the twentieth century (0.19°C/decade) is twice as large as in the full analysis period (1901–2014; 0.10°C/decade). Multidecadal climate variability results in considerable uncertainties in the regional temperature trend, but the multidecadal variability does not represent a statistically significant trend. Globally, the spatial pattern of trends is most similar among ensemble members of the same model, then among climate models, and the least similar between models and observations. The structural uncertainty and internal variability of climate models provide a range of temperature trends that generally encompass the regional scale observations. Some single model large ensembles also have variability comparable to the multimodel large ensemble, encompassing the regional scale observations. Plain Language Summary: Global warming has accelerated in the second half of the twentieth century. The spatial pattern of trends is most similar among the same model's ensemble members, then among climate models, and the least similar between models and observations. Climate models also show a better pattern correlation with the observed regional trend in the second half of the 20th century than the full analysis period (1901–2014). A multimodel Coupled Model Intercomparison Project Phase 6 large ensemble captures the observed temperature variations in the Southeastern United States better than the single model large ensemble experiments. Key Points: Global warming has accelerated in the second half of the twentieth century Spatial pattern of trends is most similar among ensemble members of the same model, and least similar between models and observations The range of simulated temperature trends in Coupled Model Intercomparison Project Phase 6 climate models generally encompass the regional scale observations